Synthesis, crystal structure, magnetic, spectroscopic, and theoretical investigations of two new nitronyl-nitroxide complexes. Issue 1 (8th January 2021) - Spinu, Cristian Andrei; Pichon, Céline; Ionita, Gabriela; Mocanu, Teodora; Calancea, Sergiu; Raduca, Mihai; Sutter, Jean-Pascal; Hillebrand, Mihaela; Andruh, Marius
Abstract: Two mononuclear complexes [(Et3 NH)[M(hfac)2 L] (M = Ni, 1 ; Zn, 2 ) have been synthesized using a nitronyl-nitroxide radical substituted nitrophenol, that is 2-(2-hydroxy-3-methoxy-5-nitrophenyl)-4, 4, 5, 5-tetramethyl-4, 5-dihydro-1 H -imidazol-3-oxide-1-oxyl, HL, as a proligand. The crystal structures of 1 and 2 have been solved and indicate an octahedral coordination geometry of the metal ions. The magnetic behavior for 1 is characterized by a strong antiferromagnetic metal–radical interaction ( J = −351 ± 1 cm −1 ; H = − J S Ni S Rad ). This exchange interaction was rationalized by DFT calculations. The EPR spectra recorded in both solution and solid state at 120 K confirm the S = ½ ground state for 1 . Graphical Abstract: